KOLABORASI ANTARA KAFE BERTEMA UNITY IN SIMILARITY DAN KANTOR TRAVEL AGENT DENGAN TEMA FIRST IMPRESSION - Suhartono, Sisca Natalia; Istanto, Freddy Handoko; Prihatmanti, Rani (KREASI, 2017)
Industries nowadays such as foods and beverages are growing rapidly. The growth is triggered by public’s necessity in needing an informal places for socializing. This happens because there is a shift in a lifestyle especially in foods and beverages’ market demands, which was originally just to come and dine becoming to dine and socialize. Today the industry players of these industries are insisted by public to present a different concept and atmosphere to answer the customers’ needs and one of them is through interior design. With a good display and a supportive interior design, it will attract public and will give a convenience for customers. Based on existing opportunities, CONCEPTICO Interior Design Consultant offers an interior design service to answer public’s needs especially on a commercial projects such as cafes and restaurants. According to the CONCEPTICO Interior Design Consultant’s service, therefore the Noodle Bar and the Agra Travel Agency, which located in Mojokerto, become one of the exact case studies. This business is from the previous business which will be developed, however the interior design has not designed yet. Therefore to solve the problem, CONCEPTICO Interior Design Consultant gives solution by providing a good services by paying attention to spatial, layouts, aesthetics, circulations, and concepts or styles which will be created.